Biochar Amendment as a Mitigation Against Freezing–Thawing Effects on Soil Hydraulic Properties - Zhongkui Chen; Chitipat Intraravimonmata; Viroon Kamchoom; Rui Chen; Natdanai Sinsamutpadung (Agronomy)
Seasonal freeze–thaw cycles compromise soil structure, thereby increasing hydraulic conductivity but diminishing water retention capacity—both of which are essential for sustaining crop health and nutrient retention in agricultural soils. Prior research has suggested that biochar may alleviate these detrimental effects; however; further investigation into its influence on soil hydraulic properties through freeze–thaw cycles is essential. This study explores the impact of freeze–thaw cycles on the soil water retention and hydraulic conductivity and evaluates the potential of peanut shell biochar to mitigate these effects. Peanut shell biochar was used, and its effects on soil water retention and unsaturated hydraulic conductivity were evaluated through evaporation tests. The findings indicate that freeze–thaw cycles predominantly affect clay’s ability to retain water and control hydraulic conductivity by generating macropores and fissures; with a notable increase in conductivity at high matric potentials. The impact lessens as matric potential decreases below −30 kPa, resulting in smaller differences in conductivity. Introducing biochar helps mitigate these effects by converting large pores into smaller micro- or meso-pores, effectively increasing water retention, especially at higher content of biochar. While biochar’s impact is more pronounced at higher matric potentials, it also significantly reduces conductivity at lower potentials. The total porosity of the soil increased under low biochar application rates (0% and 1%) but declined at higher application rates (2% and 3%) as the number of freeze–thaw cycles increased. Furthermore, the characteristics of soil deformation during freeze–thaw cycles shifted from frost heaving to thaw settlement with increasing biochar application rates. Notably, an optimal biochar application rate was observed to mitigate soil deformation induced by freeze–thaw processes. These findings contribute to the scientific understanding necessary for the development and management of sustainable agricultural soil systems.